PENGGUNAAN PENANDA MOLEKULER RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) UNTUK ANALISIS KERAGAMAN GENETIK KELAPA WEST AFRICAN TALL (WAT) - Lengkong, Edy F.; Runtunuwu, S. D. (Universitas Sam Ratulangi, 2005)
ABSTRACT Lengkong, E.F. and S.D. Runtunuwu. 2005. Use of Molecular Marker Random Amplified Polymorphic DNA (RAPD) to Genetic Diversity Analysis of West African Tall (WAT) Coconut. Eugenia 11 (3):210-217. Â Information on genetic diversity of crop gemplasm has several important implications for plant breeder. Among others is to help the breeders to decide what sources to cross so as to making new genetic combination. The use of molecular marker to genetic diversity analysis on DNA level is usefull, because it provides an opportunity to more precisely measure genetic relationships as well is not affected by the environment. The objective of this research was to analyze genetic diversity of West African Tall (WAT) using molecular marker RAPD. Five arbitrary 10-mer primers were used to amplify total DNA genom, and to generate 44 band DNA with 26 band or 59 % were polymorphic band. It was revealed that genetic diversity within population of WAT coconut was 14 %. Based on cluster analysis, at the genetic similarity 85% or genetic diversity 15 % the population was separated on three clusters. This research concluded that the population of WAT coconut grown from open pollinated seeds has different genotype one each others. Keywords: West African Tall (WAT), Coconut, RAPD